2013
DOI: 10.1371/journal.pone.0070471
|View full text |Cite
|
Sign up to set email alerts
|

Is Midlife Occupational Physical Activity Related to Disability in Old Age? The SNAC-Kungsholmen Study

Abstract: ObjectivesLeisure-time physical activity (PA) has been established to be related to more years lived without disability. However, less is known about the relationship between occupational PA and disability in old age. The aim of the study was 1) to investigate whether midlife occupational PA is related to late-life disability, and 2) to test the hypothesis that the association differs according to the occupational categories of blue and white collar work.MethodsThe study population was derived from the Swedish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
3
14
2
Order By: Relevance
“…Even though studies on the association between work-related exposures in working life and disability are limited, there is a lack of consistency in the findings. The results of our study contradict the findings of a Swedish study, which reported that occupational physical activity had no significant association with ADL disability (35). In our study, biomechanical exposure, which includes frequent occupational physical activities, was associated with high likelihood of higher disability.…”
Section: Discussioncontrasting
confidence: 99%
“…Even though studies on the association between work-related exposures in working life and disability are limited, there is a lack of consistency in the findings. The results of our study contradict the findings of a Swedish study, which reported that occupational physical activity had no significant association with ADL disability (35). In our study, biomechanical exposure, which includes frequent occupational physical activities, was associated with high likelihood of higher disability.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies also support the results of the current study, showing that strenuous work increases the risk of poor physical functioning later in life . In contrast to the current results, a previous study did not find any effect of midlife occupational PA on disability in elderly adults . There are many factors that could explain the lack of association reported in that study.…”
Section: Discussionsupporting
confidence: 85%
“…Office work is an occupation with low occupational physical strain and some occupational psychosocial strain, but the risk of later life disability due to this job profile was not attenuated by other confounding factors. This finding in our study supports the prediction of physical functioning difficulties of later life by workrelated factors among women in the French GAZEL cohort (Sabbath et al 2013), but contradicts those of an earlier study reporting that midlife moderate occupational physical activity in white-collar workers was associated with a decreased risk of later life disability (Rydwik et al 2013). Although occupational hazards may have no adverse effect on a person's physical functioning while that person is occupationally active, they may eventually lead to functional decline and disability years later or after retirement (McCarthy et al 2013;Kenny et al 2008;Cassou et al 1992).…”
Section: Discussioncontrasting
confidence: 60%
“…In a study in Ireland, McCarthy et al (2013) found that physically demanding work history was associated with ADL disability allowing for relative weight among 328 subjects, particularly in the 70-80-year-olds, in a cross-sectional analysis. On the contrary, a study among a random sample of urban Swedes (Rydwik et al 2013) showed no association of retrospectively assessed occupational physical activity in midlife with personal or instrumental ADL disability in old age in an analysis comprising 1809 subjects and adjusted for demographic and socioeconomic factors.…”
Section: Introductionmentioning
confidence: 87%